When the World Becomes Female : Guises of a South Indian Goddess - Flueckiger, Joyce Burkhalter (Book collections on Project MUSE., 2013)
During the goddess Gangamma's festival in the town of Tirupati, lower-caste men take guises of the goddess, and the streets are filled with men wearing saris, braids, and female jewelry. By contrast, women participate by intensifying the rituals they perform for Gangamma throughout the year, such as cooking and offering food. Joyce Burkhalter Flueckiger argues that within the festival ultimate reality is imagined as female and women identify with the goddess, whose power they share. Vivid accounts by male and female participants offer new insights into Gangamma's traditions and the nature of Hindu village goddesses.